Extracellular vesicles and Duchenne muscular dystrophy pathology: Modulators of disease progression - Yedigaryan, Laura; Sampaolesi, Maurilio (Frontiers in Physiology, 2023)
Duchenne muscular dystrophy (DMD) is a devastating disorder and is considered to be one of the worst forms of inherited muscular dystrophies. DMD occurs as a result of mutations in the dystrophin gene, leading to progressive muscle fiber degradation and weakness. Although DMD pathology has been studied for many years, there are aspects of disease pathogenesis and progression that have not been thoroughly explored yet. The underlying issue with this is that the development of further effective therapies becomes stalled. It is becoming more evident that extracellular vesicles (EVs) may contribute to DMD pathology. EVs are vesicles secreted by cells that exert a multitude of effects via their lipid, protein, and RNA cargo. EV cargo (especially microRNAs) is also said to be a good biomarker for identifying the status of specific pathological processes that occur in dystrophic muscle, such as fibrosis, degeneration, inflammation, adipogenic degeneration, and dilated cardiomyopathy. On the other hand, EVs are becoming more prominent vehicles for custom-engineered cargos. In this review, we will discuss the possible contribution of EVs to DMD pathology, their potential use as biomarkers, and the therapeutic efficacy of both, EV secretion inhibition and custom-engineered cargo delivery.